The Spartan Army - Lazenby, John F. 1934- (Pen, 2012)
For at least two centuries the Spartan army was the most formidable war machine in Greece; the purpose of this book is to show the reasons for this. Professor Lazenby looks first at the composition, training and organization of the army, tracing its roots back to the eighth century BC. The second part analyses some of the main campaigns - Thermopylae, Plataea, Sphakteria, Mantineia, The Nemea, Koroneia, Lechaion and Leuktra. The final part continues the story to the end of Greek independence. Since this book was first written over 25 years ago, novels, computer games and films such as 300 have raised interest in the Spartan military to new heights. The return to print of this excellent study is sure to interest academics and more general readers alike
"First published in Great Britain in 1985 by Aris & Phillips Ltd."--Title page verso. - Copyright 1985, 2012
Includes bibliographical references and index
Keywords: Military art and science / Greece / Sparta (Extinct city) / History; Geschichte; Heer; Militär; Sparta (Extinct city) / History, Military; Griechenland; Sparta